1997
DOI: 10.1038/sj.bjp.0701147
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the inhibition by acetylshikonin of the respiratory burst in rat neutrophils

Abstract: 1 The ability of acetylshikonin to inhibit the respiratory burst in rat neutrophils was characterized and the underlying mechanism of action was also assessed in the present study. 2 Acetylshikonin caused an irreversible and a concentration-dependent inhibition of formylmethionylleucyl-phenylalanine (fMLP) plus dihydrocytochalasin B (CB)-and phorbol 12-myristate 13-acetate (PMA)-induced superoxide anion (O 2 .7) generation with IC 50 values of 0.48+0.03 and 0.39+0.03 mM, respectively. Acetylshikonin also in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Consequently, shikonin effects based on Syk and Lyn inactivation would be extensive to cells where these kinases are expressed. This might be the case of a previously reported prevention by acetylshikonin of mast cell degranulation in the hind-paw edema model [8], as well as the inhibition of neutrophil respiratory burst caused by impaired tyrosine phosphorylation reactions [14]. Also, the previously reported inhibition of PLC activity in neutrophils by acetylshikonin [15] might involve targeting of Syk, because Syk is the upstream kinase that phosphorylates PLC leading to its activation [23].…”
Section: Implications Of Present Findings With Inhibitory Effects Of mentioning
confidence: 95%
See 1 more Smart Citation
“…Consequently, shikonin effects based on Syk and Lyn inactivation would be extensive to cells where these kinases are expressed. This might be the case of a previously reported prevention by acetylshikonin of mast cell degranulation in the hind-paw edema model [8], as well as the inhibition of neutrophil respiratory burst caused by impaired tyrosine phosphorylation reactions [14]. Also, the previously reported inhibition of PLC activity in neutrophils by acetylshikonin [15] might involve targeting of Syk, because Syk is the upstream kinase that phosphorylates PLC leading to its activation [23].…”
Section: Implications Of Present Findings With Inhibitory Effects Of mentioning
confidence: 95%
“…Chen et al showed another possibility, that shikonin blocks chemokine binding to CC chemokine receptor-1 [11]. Other effects that might contribute for the anti-inflammatory activity of shikonins are the prevention of leukotriene B4 biosynthesis in leukocytes [12], inhibition of superoxide-generating activity [13,14] and impairment of phosphatidylinositol signaling in neutrophils [15]. Acetylshikonin was found to suppress histamine release from rat peritoneal mast cells stimulated with compound 48/80 [8], a classical mast cell secretagogue which directly activates GTP-binding protein and induces phospholipase C-related cell signaling [16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that acetylshikonin, one of the shikonin derivatives, is effective against sterilized and infected wounds [7,8] . It has been demonstrated that acetylshikonin can inhibit tumor-induced cutaneous angiogenesis [9] and has obvious antitumor effects on S180 sarcoma model [10] .…”
Section: Introductionmentioning
confidence: 99%
“…A finding against reactivity of shikonin with O 2 •− was that acetylshikonin was unable to scavenge O 2 •− produced by the dihydroxyfumaric acid autoxidation as detected by nitroblue tetrazolium reduction. ( 40 ) In this assay, no substantial kinetic competition would be expected from nitroblue tetrazolium having a slower rate constant for the reaction with O 2 •− (5 × 10 4 M −1 s −1 ) ( 41 ) than that estimated for the reaction with shikonin. The reason for the inability of shikonin to prevent this reaction needs further elucidation.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies also suggested failure in the assembly of Nox2 system in acetylshikonin-treated neutrophils due to an impaired translocation of cytosolic p47 phox to the membranes. ( 40 ) Whatever the mechanisms of the inhibition, the fact that shikonin inhibits respiratory burst of neutrophils before activation could have implications in its effects in vivo , in modulation of inflammation-related events.…”
Section: Discussionmentioning
confidence: 99%